Evaluating Treatment Characteristics and Outcomes for Juvenile Sexual Offenders: A Review - Avezahra, Mutia Husna; Hasmy, Zulfauzy Abu (KnE Social Sciences, 2024)
Improving treatment effectiveness for adolescent sexual offenders is believed to be able to reduce the number of recidivism. This review aims to evaluate treatment characteristics and outcomes for the juvenile sexual offender. Existing treatments focus on sexual behavior management, primarily with cognitive behavioral theory and social learning theory. This study used EBSCO databases related to psychology science, such as Academic Search Complete, APA PsycArticles, MEDLINE, and APA PsycINFO. The search was for peer-reviewed empirical studies published between January 2010 and February 2020 with the inclusion criteria that focus on the treatment outcomes evaluations. Eleven studies categorized as mixed therapy programs, family-based treatments, and other specific treatments were reviewed and revealed limitations in methodology, which contributes to the obstruction of treatment evaluation. The key finding of this study suggests the developmental aspect of juvenile sexual offenders when designing interventions and effectivity measurements. Previous treatments for juvenile sexual offenders have developed with several approaches, such as cognitive behavioral perspectives and social learning theory. Keywords: juvenile sexual offender ( JSO), treatment, treatment evaluation